ZigBee technology in precision agriculture - Bakó, Károly István (Acta Agraria Debreceniensis, 2012)
ZigBee technology aims to completely satisfy the requirements set by precision agriculture, since this system makes it possible to collect data in an accurate and regular way. The cost of one module is rather favourable; therefore, damaged parts can be replaced quickly. Due to the modular structure, the system can be further developed easily. New units can be quickly incorporated into the network without any difficulty.